The role of Indonesian government in middle east conflict resolution: consistent diplomacy or strategic shifts? - Setiawati, Siti Mutiah (Frontiers in Political Science, 2024)
Indonesia and Middle East countries are associated by a shared characteristic in the form of Islam, despite the geographical separation and cultural and ethnic distinctions. Since gaining independence in 1945, Indonesia has consistently advocated for the peaceful resolution of conflict in Middle East, including Palestinian/Arab-Israeli conflict. Therefore, the objective of this study is to explore the motivations behind Indonesia's consistent support for Middle Eastern conflict resolution. Although the Indonesian government is eager to further its interest in the conflict resolution process, it is also compelled by the constitution to uphold the "Free and Active" foreign policy axiom, which essentially restricts Indonesia from taking on a side, and to maintain cordial ties with the parties involved. These principles prevent Indonesia from favoring one side and maintain positive relations with both conflicting parties. Indonesia has often played a passive role as a facilitator or participant in conflict resolution attempts rather than actively taking on the role of a mediator. The unwavering commitment to resolving Middle East conflict mostly comes from Islamic solidarity with a predominantly Muslim population and as a fellow developing country, rather than being solely based on its constitution. Alternatively, this sense of unity may also derive from the notion of solidarity in Global South.